A cross-cultural analysis of spiritual transcendence and its impact on job satisfaction, job security, and life satisfaction in Bali and Türkiye: mediator effect of earthquake anxiety - Subawa, Nyoman Sri; Baykal, Elif; Basmantra, Ida Nyoman; Mimaki, Caren Angellina; Yorulmaz, Halil (Frontiers in Psychology, 2024)
Earthquakes are considered as a major factor causing PTSD, anxiety, and depression across various age groups. Increased anxiety stemming from earthquakes may prompt individuals to turn to spirituality as a coping mechanism, with spiritual transcendence believed to be an effective way to mitigate anxiety. In this study, Bali, which has a Far Eastern spiritual tradition, and Türkiye, the majority of whose population is Muslim, are discussed comparatively. In fact, the underlying reason for this choice is to examine whether there is a difference between Hindu belief, one of the Far Eastern religions as a spiritual tradition, and Islam, one of the monotheistic religions, regarding individuals’ ability to manage anxiety and some basic psychological reactions to the fear of earthquakes. An example of Bali’s Hindu tradition has been considered a representation of the Islamic tradition, one of the monotheistic religions in Türkiye. Given this phenomenon, the study took a quantitative approach, giving a novel conceptual framework for understanding the relationship between spiritual transcendence, seismic fear, job satisfaction, job security, life satisfaction, and the moderating influence of optimism. Empirical data were acquired via surveys issued via Google Form to a total of 913 workers in Bali and Türkiye. The research data were analyzed using SmartPLS software and a structural equation modeling technique. Findings indicate that earthquake anxiety and the impact of spiritual transcendence on satisfaction and job security are stronger in Bali than in Türkiye. Additionally, spirituality holds greater significance for the Balinese sample compared to the Turkish sample. The study clarifies the implications of its findings and provides guidance for future research endeavors.